1986
DOI: 10.1097/00132586-198604000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Warming Blood Before Transfusion. Does Immersion Warming Change Blood Composition?

Abstract: The practice of warming blood for transfusion by immersion in a water bath has been studied. Blood, 3 days after collection, with CPD-adenine anticoagulant, was warmed at 2s"C. 3 P C and 4s"C for up to 2 hours. The procedure was repeated after 2 and 4 weeks' storage at 4'C. Only trivial biochemical and morphological changes resulted from warming. Within these limits. immersion warming of blood appears to be a reasonable alternative to using a blood-warming coil. Other aspects of immersion warming are discussed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…One study using immersion-warming techniques found biochemical markers of haemolysis when blood was warmed at 45°C [37]. A later study utilising microwave blood warming concluded that the safe upper limit to heat blood was 49°C [38].…”
Section: Safety Concernsmentioning
confidence: 99%
“…One study using immersion-warming techniques found biochemical markers of haemolysis when blood was warmed at 45°C [37]. A later study utilising microwave blood warming concluded that the safe upper limit to heat blood was 49°C [38].…”
Section: Safety Concernsmentioning
confidence: 99%
“…Warming of blood prior to transfusion became a common practice after the 1960's when multiple papers highlighted the dangers of cold blood transfusion [6,8], Infusion of 0.5 litre of cold blood can reduce core temperature by 0.5-1°C [9]. Infusion of 3 litres of cold blood caused a signifi cant drop in oesophageal temperature and increased the number of cardiac arrests.…”
Section: Physiological Consequences Of Transfusing Cold Bloodmentioning
confidence: 99%
“…χορήγηση ζεστών υγρών με υψηλή ταχύτητα, ενώ υπάρχουν αναφορές θανάτων από τη χρήση εγχυτή επιπέδου 1 (Adhikary et al, 1998). Εργαστηριακές μελέτες που συνέκριναν την ικανότητα των συσκευών να εξαλείφουν τον αέρα κατά τη διάρκεια της έγχυσης, η συσκευή Ranger βρέθηκε καλύτερη από τον εγχυτή επιπέδου 1 όταν εισήχθηκαν τεχνικά 50-400 ml αέρα (Schnoor et al, 2004 (Marks et al, 1985). Μια μεταγενέστερη μελέτη που χρησιμοποίησε μικροκύματα για τη θέρμανση αίματος κατέληξε στο συμπέρασμα ότι το ανώτατο όριο ασφάλειας θέρμανσης του αίματος ήταν 49 °C (Herron et al, 1997 .…”
Section: θέματα ασφάλειαςunclassified